2017
DOI: 10.1007/s00203-017-1402-1
|View full text |Cite
|
Sign up to set email alerts
|

A double-quadratic model for predicting Vibrio species in water environments of Japan

Abstract: Vibrio spp. are natural inhabitants of marine and estuarine environments. Vibrio cholerae, Vibrio parahaemolyticus, and Vibrio vulnificus are the major infectious agents for humans. Their densities are affected by environmental factors such as water temperature and salinity. The detailed contribution of each factor still remains to be elucidated. Here we conducted multi-coastal study in a 21-month period to examine relationships between environmental factors and V. cholerae, V. parahaemolyticus and V. vulnific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…These factors would control the physico-chemical characteristics of each lake, and therefore their susceptibility to constitute habitats for Vibrio cholera [67]. Consequently, the bacillus niche does not appear to be significantly different from that described in previous studies in coastal areas [2,3,5,6,68], such as the lagoon areas of India [4].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 88%
See 1 more Smart Citation
“…These factors would control the physico-chemical characteristics of each lake, and therefore their susceptibility to constitute habitats for Vibrio cholera [67]. Consequently, the bacillus niche does not appear to be significantly different from that described in previous studies in coastal areas [2,3,5,6,68], such as the lagoon areas of India [4].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 88%
“…Cholera is a severe infectious disease caused by Vibrio cholerae. This bacillus thrives in alkaline saline aquatic environments with high temperatures and rich in organic matter and plankton [1][2][3][4][5][6]. The bacillus is found in coastal areas, where fresh water from rivers mixes with salt water from the sea [1,2,[7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Vibrios have been associated with climate change and have been proposed as bioindicators of climate change in marine systems [ 55 , 56 ], and since their abundance in the water is temperature related [ 57 ], they have rapidly adaptive behavior, more than one portal of entry, and have dominated the temperate climate zone, with outbreaks occurring ever closer to the poles. Thus, it can be speculated that the Mediterranean Sea in the near future will be an ideal setting for more Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, some studies of model establishment and Vibrio prediction have been reported. Hidemasa Izumiya et al conducted a multi-coastal study to examine relationships between environmental factors and Vibrio and build a linear regression model for Vibrio prediction (Izumiya et al, 2017). Brett Froelich et al conducted a five-parameter mechanistic model to predict Vibrio abundance in the river based on environmental processes (Froelich et al, 2013).…”
Section: Vibrio Abundance Variation and The Predictive Model Construc...mentioning
confidence: 99%
“…in seawater can cause seafood-borne illnesses through consumption of contaminated seafood and cause wound infections by exposure of an open wound to seawater, probably resulting in diarrhea, septicemia and even death (Hsieh et al, 2008). The forecasting of Vibrio abundance and breakout would help to prevent human illness by identifying and reporting the forecasting information and making it publicly available (Froelich et al, 2013;Izumiya et al, 2017).…”
Section: Introductionmentioning
confidence: 99%